Influências ecológicas nas distâncias percorridas dos Muriquis-do-norte (Brachyteles hypoxanthus) - Moura, Letícia Almeida (2019)
Understanding the ecological factors that influence the daily routes of animals provide us with valuable information on how they invest their time and energy in their daily decision making. The proportion of time invested in the development of each activity may change according to the social system of the group, climatic variations and conditions of the environment, influencing the daily distance traveled. In this sense, primates are great models to be studied because they can respond to environmental conditions in various ways. For example, the use of terrestrial strata by arboreal primates represents a way of acquiring resources, especially in fragmented habitats where opportunities to expand their range are constrained. In this study, we investigate how ecological factors, including ground use, can influence the daily distance traveled by a group of Northern Muriquis (Brachyteles hypoxanthus). We will start the investigation by analyzing the relation of muriquis with the use of the ground and other vertical strata of the vegetation, and comparing the distances traveled in the days with and without the use of the ground. We expected that the smallest routes were related to the days with ingestion of food on the ground, however as the resources are not always concentrated in the same place, greater distances can also be observed. The study was conducted at RPPN - Feliciano Miguel Abdala, MG, Brazil, from August 2015 to July 2016. We used 99 days with > 8 hours of observation on one study group, totaling 1,776 scans, 9,610 records and 859.34 observation hours, including ground use on 46 days and over 102 events (including scan samples and ad libitum observations). Most of the activities were carried out mainly in the middle canopy, with only drinking water occurring primarily on the ground. Different from what we expected, the trails were larger on days with ground use for food. Similarly, the paths were larger in the days with the ingestion of water in the ground, corroborating with our alternative forecast. These results suggest that the energy or nutritional value of food can offset the energy costs of the longer routes. In addition, the need for important resources such as the water sources found on the ground can contribute to the greater distances traveled. Muriquis’ flexibility in using the floor can be an important factor in their staying in an impacted environment.